Database Systems for Advanced Applications 19th International Conference, DASFAA 2014, International Workshops: BDMA, DaMEN, SIMp3(B, UnCrowd; Bali, Indonesia, April 21--24, 2014, Revised Selected Papers - Han, Wook-Shin.; Lee, Mong Li.; Muliantara, Agus.; Sanjaya, Ngurah Agus.; Thalheim, Bernhard; Zhou, Shuigeng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the workshop proceedings of the 19th International Conference on Database Systems for Advanced Applications, DASFAA 2014, held in Bali, Indonesia, in April 2014. The volume contains papers from 4 workshops, each focusing on hot topics related to database systems and applications: the Second International Workshop on Big Data Management and Analytics, BDMA 2014; the Third International Workshop on Data Management for Emerging Network Infrastructure, DaMEN 2014; the Third International Workshop on Spatial Information Modeling, Management and Mining, SIMp3(B 2014, and the DASFAA Workshop on Uncertain and Crowdsourced Data, UnCrowd 2014.
Meme media and knowledge federation -- A framework for measure storage utilization in cloud storage systems -- Monitoring query  processing in mobile robot databases -- Uncertainty in crowd data sourcing under structural constrains.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Storage and Retrieval